Institutional Roots of Economic Decline: Lessons from Italy - Marco Simoni (London School of Economics and Political Science (LSE), European Institute, 2019)
The economic decline of Italy since the mid 1990s is a critical case in contemporary political economy because its model of capitalism was deeply reformed at the time when its decline commenced. This paper argues that economic stagnation cannot be attributed to special interest politics, nor to the lack of market-friendly reforms in a globalized economic context, as previous literature argues. Instead, Italian economic decline is a consequence of institutional change which on the one hand has destroyed previous institutional complementarities, and on the other hand has led to an incoherent, or "hybrid," setting. In the institutional spheres of corporate governance and labor, economic reforms established new institutions alternatively apt to support both strategic coordination and market coordination, resulting in institutional incoherence. In addition, building on the case of Italy and based on patent data relative to 19 OECD countries, this paper unpacks the link between institutional coherence and economic performance. It articulates a novel hypothesis according to which higher specialization in innovation patterns, derived from institutional coherence, also leads to higher overall innovation volumes. Hence, reforms that undermine a prevalent mode of coordination across the economy also undermine innovation capacity, leading to economic decline.
Keywords: 330; Varieties of Capitalism; Economic Growth; Italy